A Surfactants Walk to Work: Modes of Action of Citrate Controlling (10–10) and (000–1) Zinc Oxide Surface Growth from Solution. Issue 16 (22nd July 2016) - Milek, Theodor; Zahn, Dirk
Abstract: Molecular dynamics simulations unravel the association of citrate to (10–10) and (000–1) growth fronts of zinc oxide and demonstrate an unexpected mobility of the surfactant. Citrate association to perfectly planar (10–10) and (000–1) ZnO‐ethanol interfaces was found to be favored over dissociation by 1.5–2 eV hence suggesting strongly bound, immobilized surfactants. However, intramolecular stress prevents binding of all three carboxyl groups to planar surfaces and the typical arrangement is that of two carboxyl‐Zn contacts (including two salt bridges each) whilst the remaining carboxyl group is dangling into the solvent. As a consequence, the surfactant exhibits a "walking" mechanism to move along the surface by exchanging the role of its carboxyl groups. This finding has strong implications for the role of citrate during crystal growth as illustrated by a recently developed simulation scheme based on hundreds of individual Zn 2+ and OH – ion association steps. In particular, for the (10–10) surface – which grows via formation of ridges embedded by {10–10} faces – these simulations show how citrate ions move towards steps and bind to the growth front by additional 4 eV per surfactant molecule. Abstract :